Abdón Cifuentes, Catholic advertiser vs. the Liberal State, 1862-1890. (2014)
This study is intended to trace the trajectory of Abdón Cifuentes (1836-1928), a Catholic-Conservative Chilean political leader of the second half of the XIX century. Asa Catholic and Republican, Cifuentes struggled against liberal anticlericalism, as well as the press, the Parliament and the social activism of that time. Cifuentes assertedhis idea of society, based on the Catholic ideal whereby the Liberal State should be removed of its guarantees and rights. In order to know more about the main aspects of this Catholic-Conservative advertiser, an outline of his trajectory is presented in this article. The following section, “Building war machines” deals with the referents and struggles of Cifuentes to keep Catholic citizens in a large part of the country informed by means of the promotion of the Conservative press between 1862 and 1885. “Social-Catholic activism” is the result of Cifuentes’ unending will to instruct and organize Chilean Catholic society. Thus, since 1865, different associations encompassing youth,workers, members of the elite engaged social and charity work, and the great Catholic Union was created to oppose the desacralization of marriage and cemeteries, betweenthe years of 1883 and 1888. Conclusions are drawn at the end of this study.